Question

Iet IsHerm = a
[
begin{array}{c}
text { common diff }=d
text { Sum of frst Pterms }=frac{P}{2}(29+(R-1) d) ldots(1)
end{array}
]
and sumof furst q tems ( =frac{q}{2}(29+(9-1) d)--(2) )
According to ques.
[
begin{array}{l}
quad P(2 a+(p-1) d)=frac{q}{2 a(p-q)-d{q(q-1)-P(p-1)=0}
2 a(p-q)-dleft[q^{2}-p^{2}+(p-q)right]=0
(p-q)(2 a+d(p+q-1)]=0
2 a+d(p+q-1)=0 quad[sin (e p eq a) ldots
end{array}
]
Now the sum of ( 6 mathrm{r} 1+cdot(mathrm{P}+mathrm{a}) ) terms ( 1 mathrm{S} )
[
frac{p+q}{2}(2 a+(p+q-1) d]=0
]
( therefore quad ) Ans ( rightarrow 0 ) opton

# 8. If the sum of an AP is the same for p terms as for q terms, then find out the sum for (p+q) terms? (a) 2 (b) 0 (c) 4 (d) None of these None of these

Solution